Residue Number System Truth-Table Look-Up Processing-Moduli Selection and Logical Minimization - GUEST, C. C; MIRSALEHI, M. M; GAYLORD, T. K (IEEE transactions on computers, 1984)
Truth table look-up processing using binary coded residue numbers is investigated for full-precision addition and multiplication for implementations using either electronic or optical technologies. The logically minimized numbers of input combinations needed for each operation are presented for moduli 2-23. The moduli sets that require the minimum number of reference patterns are determined for addition and multiplication of 4, 8, 12, and 16 bit words.